Effect of Combined Urea and Calcium Nitrate Application on Wheat Tiller Development, Nitrogen Use Efficiency, and Grain Yield - Chao Wang; Haixing Cui; Min Jin; Jiayu Wang; Chunhui Li; Yongli Luo; Yong Li; Zhenlin Wang (Plants)
Optimizing nitrogen (N) sources has the potential to improve wheat tillering, nitrogen use efficiency (NUE), and grain yield, yet the underlying mechanisms remain unclear. This study hypothesizes that combining specific N sources can increase zeatin riboside + zeatin (ZR + ZT) content in tiller nodes and maintain a higher ZR + ZT/gibberellin A7 (GA7) ratio, thereby promoting tiller development, enhancing NUE, and increasing yield. The effects of N source treatments on two wheat cultivars, the multi-spike Shannong 28 (SN28) and the large-spike Tainong 18 (TN18), were investigated. A total of seven N treatments were tested: no nitrogen (N0), urea (N1), calcium nitrate (N2), ammonium chloride (N3), and equal doses of urea and calcium nitrate (N4), urea and ammonium chloride (N5), and calcium nitrate and ammonium chloride (N6). The results showed that treatment N4 significantly increased the levels of ZR and ZT in tiller nodes, while maintaining a higher ZR + ZT to GA7 ratio. This hormonal shift promoted tiller formation and biomass accumulation. Under N4, both cultivars exhibited the highest number of effective spikes and biomass in higher-order tillers. N4 also enhanced N accumulation in the grains, N absorption efficiency, and N translocation, while reducing N loss. Compared to N1, effective spike numbers increased by 7.8% in SN28 and 5.6% in TN18, resulting in a 6.4% increase in grain yield for SN28 and a 2.2% increase for TN18. In conclusion, the combined application of urea and calcium nitrate optimizes hormonal regulation, improves NUE, and significantly enhances wheat tillering and grain yield, providing a promising strategy for enhancing wheat productivity.